Effect of electric stimulus on human adipose-derived mesenchymal stem cells cultured in 3D-printed scaffolds - ŞAHİN, ALİ; YILMAZ, BETÜL; GÜNDÜZ, OĞUZHAN; GÜVENÇ, YAHYA (WILEY, 2021)
Electrical stimulation has shown great potential for nerve regeneration processes. This makes it attractive to use electrically active materials in the neural scaffold. In this paper, bismuth ferrite (BFO) nanoparticles were synthesized via co-precipitation method and incorporated to 10 wt% polylactic acid (PLA) in chloroform to obtain 3D-printed PLA/BFO biocomposites. The crystallinity of BFO nanoparticles was confirmed by XRD, and we studied its chemical structure with FTIR, as well as the mechanical properties of the 3D-printed composites. in vitro studies show that 3D-printed scaffolds have no cytotoxicity and support the proliferation of human adipose-derived mesenchymal stem cells (hADMSCs). Furthermore, 3D scaffolds embedded with BFO shows the highest cell viability relative to pristine PLA and BFO-lined PLA scaffolds. A 48 hours electrical stimulation on the hADMSC cultured inside the 3D-printed BFO-lined PLA scaffolds indicates that stimulated cells are aligned toward the BFO line. These results could indicate the potential of BFO for directing cells toward damaged tissues.
Keywords: 3D printing; bismuth ferrite; cell alignment; electrical stimulation; neural scaffold; STIMULATION; COMPOSITES; THERAPY; FIELD